EFFECT OF DILATATION OF THE CEREBRAL VENTRICLES AFTER THE ADMINISTRATION OF NITROXYNIL IN SWISS ALBINE MICE DURING ORGANOGENESIS - Queiroz, Gustavo Rodrigues; Cunha Filho, Luiz Fernando Coelho da; Zanluchi, Aline Tramontini; Barca Junior, Flávio Antonio; Okano, Werner (Archives of Veterinary Science, 2012)
SUMMARY: Nitroxynil 34% is an anthelmintic of the family of phenolic substitutes that is used for the control of